OPTIMALISASI STRATEGI PEMASARAN MUDHARABAH MELALUI EDUKASI DAN ANALISIS REGRESI DI BSI KCP MEDAN ADAM MALIK: STRATEGI PEMASARAN MUDHARABAH - Febya Br Nasution; Rafika Sari Prayetno; MHD Pradana; Rima Aprilia (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
This community service activity aims to improve the effectiveness of marketing strategies for mudharabah savings products at Bank Syariah Indonesia (BSI) KCP Medan Adam Malik. The main problem faced by the partner institution is the low public understanding of mudharabah products and the suboptimal promotional strategies implemented by the bank. The implementation method consisted of several stages, including field observation, marketing data collection, data analysis using multiple linear regression, and educational discussions on marketing strategies with the bank staff. The data used consisted of monthly marketing data for one year analyzed using IBM SPSS Statistics 27. The results showed that simultaneously the number of promotional advertisements, the number of BSI branches in Medan City, and the profit-sharing ratio influence the number of mudharabah account openings. Partially, promotional advertisements and profit-sharing ratios significantly influence account openings, while the number of branches does not have a significant effect. Based on these findings, the service team recommends enhancing digital promotion strategies and strengthening public education on Islamic banking products. This activity is expected to assist Bank Syariah Indonesia KCP Medan Adam Malik in increasing public interest in mudharabah savings accounts.